Lifelong persistence of nuclear RNAs in the mouse brain - Zocher, Sara; McCloskey, Asako; Karasinsky, Anne; Schulte, Roberta; Friedrich, Ulrike; Lesche, Mathias; Rund, Nicole; Gage, Fred H.; Hetzer, Martin W.; Toda, Tomohisa (Science, 2024)
Genomic DNA that resides in the nuclei of mammalian neurons can be as old as the organism itself. The life span of nuclear RNAs, which are critical for proper chromatin architecture and transcription regulation, has not been determined in adult tissues. In this work, we identified and characterized nuclear RNAs that do not turn over for at least 2 years in a subset of postnatally born cells in the mouse brain. These long-lived RNAs were stably retained in nuclei in a neural cell type–specific manner and were required for the maintenance of heterochromatin. Thus, the life span of neural cells may depend on both the molecular longevity of DNA for the storage of genetic information and also the extreme stability of RNA for the functional organization of chromatin.
CRIS-Team Scopus Importer:2024-04-19